Assisting community management of groundwater: irrigator attitudes in two watersheds in Rajasthan and Gujarat, India - Varua, M.E.; Ward, J.; Maheshwari, B.; Ozac, S.; Purohit, R.; Hakimuddin; Chinnasamy, Pennan (Elsevier, 2016)
The absence of either state regulations or markets to coordinate the operation of individual wells has focussed attention on community level institutions as the primary loci for sustainable groundwater management in Rajasthan and Gujarat, India. The reported research relied on theoretical propositions that livelihood strategies, groundwater management and the propensity to cooperate are associated with the attitudinal orientations of well owners in the Meghraj and Dharta watersheds, located in Gujarat and Rajasthan respectively. The research tested the hypothesis that attitudes to groundwater management and farming practices, household income and trust levels of assisting agencies were not consistent across the watersheds, implying that a targeted approach, in contrast to default uniform programs, would assist communities craft rules to manage groundwater across multiple hydro-geological settings. Hierarchical cluster analysis of attitudes held by survey respondents revealed four statistically significant discrete clusters, supporting acceptance of the hypothesis. Further analyses revealed significant differences in farming practices, household wealth and willingness to adapt across the four groundwater management clusters. In conclusion, the need to account for attitudinal diversity is highlighted and a framework to guide the specific design of processes to assist communities craft coordinating instruments to sustainably manage local aquifers described.